Temperature and maturation stage: its effects on the germination of Jatropha seeds - Silva,Leandro Mariano da (2017)
Abstract: The present study had as objective to identify the adequate maturation stage for fruit harvest as well as the ideal temperature for germination of Jatropha curcas seeds. The fruit were collected to form a composite sample, and then classified by color in three maturity stages as follows: Stage I - yellow fruit with shiny black seeds; Stage II - yellow fruit, with more than 50% brownish black, and shiny black seeds; Stage III - dry black fruit with matt black seeds. Subsequently, evaluations of the degree of moisture, germination, electrical conductivity and water absorption at different temperatures (20, 25, 30, 35 and 40 °C). The study followed a 3x5 factorial experimental design with four replications. The maximum germination occurs at a temperature of 35 ºC, it is recommended to harvest the seeds of Jatropha curcas at maturity stage II.